2010
DOI: 10.1108/14676371011031856
|View full text |Cite
|
Sign up to set email alerts
|

The Pacific way: sustainability in higher education in the South Pacific Island nations

Abstract: Purpose -The purpose of this paper is to create an area profile of significant activity and possibility in higher education for sustainable development (ESD) in the island nations of the South Pacific Ocean. Design/methodology/approach -This is a descriptive research paper on philosophy, policy, and practice according to a methodology of categorical analysis by developments, challenges, and prospects. The focus is on higher education institutions, particularly the University of the South Pacific, the regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 5 publications
(1 reference statement)
0
14
0
Order By: Relevance
“…These included permeability of disciplines within institutions (and, thus, the ability to work interdisciplinarily), establishing a relationship between theory and practice in course work and creating space for reflection on curricula. In research on the South Pacific Island Nations, it has been found that sustainability tended to be integrated into all curricula in PSE [26]. A cross-institutional study from 2008 also found that integration of sustainability principles is on the increase across a wide range of extra-curricular activities in a number of PSE institutions within the UK [27].…”
Section: Curriculamentioning
confidence: 99%
“…These included permeability of disciplines within institutions (and, thus, the ability to work interdisciplinarily), establishing a relationship between theory and practice in course work and creating space for reflection on curricula. In research on the South Pacific Island Nations, it has been found that sustainability tended to be integrated into all curricula in PSE [26]. A cross-institutional study from 2008 also found that integration of sustainability principles is on the increase across a wide range of extra-curricular activities in a number of PSE institutions within the UK [27].…”
Section: Curriculamentioning
confidence: 99%
“…The launching of the DESD resulted in new developments in the Pacific Island region. These include the Pacific Education for Development Framework and its Action Plan for Sustainable Development in the Pacific Islands (2008-2014) (Corcoran 2010). This document identifies formal education and training as one of the priority areas, with teacher training established as an area of significance.…”
Section: Education For Sustainable Developmentmentioning
confidence: 99%
“…It is home to a diverse range of indigenous peoples and their cultures and languages. Recognition of PINs as a special sustainability case is embedded in most international sustainability agreements, which most Pacific Islands are active partners of and signatories to (Corcoran 2010).…”
Section: Sustainable Development In Pacific Island Contextsmentioning
confidence: 99%
“…Furthermore, HEIs were offered to adapt the Higher Education Sustainability Act and the United Nations Decade of Education for Sustainable Development (DESD) in 2005-2015 [2]. The UN DESD (2005 to 2015) provides a major opportunity for HEIs worldwide to address sustainability at local, national, regional and global levels [3]. Besides, ESD is an educational goal that aims to provide the present generations with the necessary knowledge, skills, competencies, and values that are crucial for societal sustainability [4].…”
Section: Introductionmentioning
confidence: 99%